Pituitary surgery: experience from a large network in Central Switzerland (Swiss Medical Weekly, 2012)
PRINCIPLES: During the past years our group built a care network for patients with pituitary tumours with referrals from the midlands and the central part of Switzerland, comprising about 1.6 million inhabitants. The purpose of this retrospective observational study with longitudinal data is to review the experience of pituitary surgery and the operative outcome within this Swiss-wide largest network. METHODS: A total of 182 patients operated at the Neurosurgical Department of the Kantonsspital Aarau 2005–2010 were included in this study. The follow-up was 3.6±1.6 years. RESULTS: The following lesions were found: non-functioning adenoma (n = 114; 63%); macroprolactinoma (n = 18; 10%); microprolactinoma (n = 11; 6%); acromegaly (n = 11; 6%), Cushing’s disease (n = 7; 4%); Rathke’s cleft cyst (RCC; n = 9; 5%); others (n = 12; 7%). Intraoperative MRI (iMRI) was used in 115 (63%) patients. Preoperatively, hypopituitarism was found in 105 (58%) patients. Postoperative recovery of defunct axes was detected in 48%. Visual field and visual acuity deficits due to optic pathway compression by tumour were detected in 48% and 41% of the patients, respectively. Postoperative recovery of visual function was seen in 89%. The increase of total resection rate by iMRI was statistically significant (p = 0.0007). Recurrent tumour growth was seen in 5 (3%) patients during follow-up. CONCLUSIONS: Transsphenoidal surgery is the primary treatment for most sellar lesions. The use of iMRI may lead to higher gross total resection rates. In Switzerland close cooperation between specialised centres is a very positive experience both to support operative case loads and to optimise patient follow-up.